Bifunctional thioacetamide-mediated synthesis of few-layered MoOSx nanosheet-modified CdS hollow spheres for efficient photocatalytic H2 production. Issue 19 (2nd September 2022) - Tao, Siqin; Zhong, Wei; Chen, Yuxiao; Chen, Feng; Wang, Ping; Yu, Huogen
Abstract : Few layered MoOS x nanosheet-decorated CdS hollow spheres have been rationally fabricated by a one-step bifunctional thioacetamide-mediated route to notably enhance the photocatalytic H2 -production performance. Abstract : Constructing efficient cocatalyst-modified hollow-structured photocatalysts holds great potential in the photocatalytic H2 evolution field. Regrettably, it still remains a formidable challenge to develop cost-effective cocatalysts and explore simple synthetic methods for their scalable applications. Herein, a novel one-step strategy of bifunctional thioacetamide-mediated synthesis has been developed to synthesize few-layered MoOS x nanosheet-modified CdS hollow sphere photocatalysts (MoOS x /CdS). In this case, the MoOS x nanosheets exhibit a typical few-layered structure of 3–7 layers and are homogeneously attached to the surface of the CdS hollow spheres. It is observed that the few-layered MoOS x /CdS (1 wt%) hollow sphere photocatalysts obtain the highest photocatalytic H2 -evolution rate of 929.40 μmol h −1 g −1, which is far beyond that of the blank CdS sample by a factor of 3.7. The in situ X-ray photoelectron spectroscopy (XPS) and density functional theory (DFT) analyses confirm that the well-designed few-layered MoOS x cocatalysts can efficiently suppress photoexcited carrier recombination and provide abundant electron-deficient S sites to speed up the interfacial H2 -evolution reaction, thus improving the photocatalytic H2 -generation efficiency of the CdS photocatalysts. This study opens a new window into the fabrication of non-precious metal cocatalyst-modified hollow structures with remarkably promoted photocatalytic H2 -production activity.